Cytology of the Mediastinum and Gut Via Endoscopic Ultrasound-Guided Aspiration - Bardales, Ricardo H. (Essentials in Cytopathology, 2015)
This text provides a comprehensive review of the cytology of disease processes of the mediastinum and mediastinal lymph nodes with emphasis in lung and gut nodal cancer staging in specimens obtained by EUS-FNA. This book also reviews the cytology of intramural masses of the gastrointestinal tract using a pattern-based diagnostic approach. The cytomorphology of lesions obtained by EUS-FNA is peculiar by the common presence in the obtained sample of normal luminal gastrointestinal contents, and the cytopathologist should be familiar with this pattern not often seen when the sampling is done by percutaneous approach. Technical considerations pertaining to the operator performing the procedure as well as to the cytopathologist, with emphasis on rapid on-site interpretation are also covered. Most lesions described in the book also have endoscopic US image correlation.   CYTOLOGY OF THE MEDIASTINUM AND GUT VIA ENDOSCOPIC ULTRASOUND-GUIDED ASPIRATION is a useful and practical guide for cytological interpretation and differential diagnosis of lesions obtained by EUS-FNA of mediastinum and gut. All chapters are written by experts with many years of experience in the field and contain the cytology, immuno-profile, molecular profile, and ultrasound features of the masses described. This book is a valuable source of information for cytopathologists, cytopathology fellows, cytotechnology students and upper level pathology residents. Echoendoscopists, and any professional with interest in ultrasound and fine-needle aspiration cytology of mediastinal and GI masses will benefit from this book.